A Buddhist Approach to International Relations Radical Interdependence - Long, William J. (Springer Nature, 2021)
This book is an open access book. Many scholars have wondered if a non-Western theory of international politics founded on different premises, be it from Asia or from the "Global South," could release international relations from the grip of a Western, "Westphalian" model. This book argues that a Buddhist approach to international relations could provide a genuine alternative. Because of its distinctive philosophical positions and its unique understanding of reality, human nature and political behavior, a Buddhist theory of IR offers a way out of this dilemma, a means for transcending the Westphalian predicament. The author explains this Buddhist IR model, beginning with its philosophical foundations up through its ideas about politics, economics and statecraft.